Medieval intersectionality: uncovering fluid identities in thirteenth and fourteenth century Castilian epic poetry - De Souza, Rebecca (2018)
This thesis assesses two major texts from the epic corpus of medieval Iberia: the Poema de mio Cid and two chronicle redactions of the Siete Infantes de Lara, with the aim of uncovering the way in which the epic poets unconsciously acknowledge the fluid, contextually-contingent nature of identity that evolves according to circumstance. The poetry is, as one would expect, entirely at odds with the models of identity presented in the officialised discourse found in the legal and political texts of their contemporary Iberia, as well as inherited classical and patristic models. It is the first analysis of its kind to depart from a narrow analysis of identity in the epic texts that is solely predicated upon either gender, cultural, religious or social difference. These socialised categories of identity are discussed simultaneously in order to assess the way in which socio-cultural background shifts the dynamics of power within and across characters of both genders. This method is inherently intersectional, and is one that untangles the complexity of defining the self in a pluricultural society within permeable borders next to al-Andalus.